Bonding, bridging and linking social capital and empowerment among squatter settlements in Tehran, Iran - Babaei, Hamidreza; Ahmad, Nobaya; Gill, Sarjit S. (IDOSI Publications, 2012)
This study aims to determine the effect of bonding, bridging and linking social capital on the empowerment among squatter settlements in Tehran, Iran. The sample comprised 328 poor people in two communities from Iran, which were randomly selected for the study. A self-administered questionnaire was used as the data collection method. The perceived bonding, bridging and linking social capital was measured by the trust and relationship with family and close friends and with colleagues, neighborhood people and society people as well as with the ethnic group and governmental and non-governmental organizations. In addition, the perceived empowerment was measured by summing the scores of psychological and financial assets. The results revealed the significant effect of bonding, bridging and linking social capital on empowerment among squatter settlements. Bonding social capital had the largest beta coefficient compared to other dimensions, such as bridging and linking social capital.